Optical and magnetic properties of small-size core–shell Fe3O4@C nanoparticles. (December 2021) - Chen, Xifang; Zhou, Yue; Han, Hongwen; Wang, Xiaoyu; Zhou, Lei; Yi, Zao; Fu, Zhenjin; Wu, Xianwen; Li, Gongfa; Zeng, Liangcai
Abstract: Core–shell Fe3 O4 @C magnetic nanoparticles which are of great interest for research have a widely applied prospect. However, people know little about the optical and magnetic properties of the small-size Fe3 O4 @C nanoparticles due to the difficulty of uniformly coating small size Fe3 O4 nanoparticles. In this paper, the influence of carbon shell coating on the optical and magnetic properties of small size Fe3 O4 nanoparticles was presented. Carbon coating can strengthen the absorption intensity in the UV–visible light region through the introduction of oxygen defects on the surface of the nanoparticles by nitric acid treatment. Fe3 O4 and Fe3 O4 @C nanoparticles both display typical superparamagnetic behavior in the high-temperature regime and a blocked state at low temperature from hysteresis loop, zero-field cooled and field cooled curves. Carbon coating reduce the surface uniaxial anisotropy, thus the average blocking temperature B > decreases from 59 K of Fe3 O4 nanoparticles to 50 K of Fe3 O4 @C nanoparticles. Highlights: Fe3 O4 @C nanoparticles exhibit a wide range of light absorption in the UV-visible region. Fe3 O4 @C nanoparticles display typical superparamagnetic behavior in the high-temperature regime. Fe3 O4 @C nanoparticles have a blocked state at temperature lower than 50 K. Fe3 O4 @C nanoparticles have lower average blocking temperature because carbon coating can reduce the surface anisotropy.